Microbial electrosynthesis of carboxylic acids through CO2 reduction with selectively enriched biocatalyst: Microbial dynamics. (July 2017) - Modestra, J. Annie; Mohan, S. Venkata
Graphical abstract: Schematic representation of experimental methodology adopted during the study for bio-electrochemical reduction of CO2 towards carboxylic acids synthesis through homoacetogenic bacteria enrichment Highlights: Heat pretreatment enriched stable bacterial community for carboxylic acids synthesis. Higher acetic acid production of 12.57 mM was noticed in BESH . Energy discharge portrayed as BES potential is high in response to applied voltage. Electron carriers for bioelectrosynthesis were noticed during voltammetric analysis. Abstract: Microbial electrosynthesis is an emerging strategy of transforming CO2 into valuable chemicals by exploiting the capabilities of bacteria. As biocatalyst is considered as prime factor in bioelectrochemical CO2 reduction, we used an enrichment technique comprising of heat pretreatment of parent inoculum followed by enrichment under gas mixture of H2 and CO2 . Here, we use a double chambered bioelectrochemical system (BESH ) wherein cathode chamber was inoculated with enriched acetogenic (homoacetogenic) bacteria, subsequently polarized with voltage of −0.8 V vs Ag/AgCl (s). BESH operation resulted in synthesis of carboxylic acids/volatile fatty acids (VFA), with major proportion confined to production of acetic acid (12.57 mM) with a maximum current density of 650 ± 50 mA/m 2 generated in response to applied voltage. While in the previous study, BESC (untreated) depicted comparatively low yield of acetic acid (3.19 mM). A maximum of 67% reduction in bicarbonate concentration and columbic efficiency of 38% was noticed signifying the utilization of inorganic carbon for bio-electrochemical synthesis of acetic acid. Efficiency of BES was also discussed in terms of energy discharge. Few signals were obtained on voltammetric signature at various potentials which might correspond to the redox potential of cytochromes, flavo proteins and Fe-S proteins suggesting their involvement as electron carriers during microbial electrosynthesis. Phylogenetic analysis was comparatively made between untreated and heat treated enriched bacteria which revealed members belonging to Clostridiaceae dominant in heat treated inoculum, while methanogens appeared in untreated inoculum. Selective enrichment of biocatalyst proves to be advantageous for CO2 reduction in BES which yielded high productivity of carboxylic acids in comparison to untreated biocatalyst.